The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/pds.4953
|View full text |Cite
|
Sign up to set email alerts
|

Treatment indications for antidepressants prescribed to pregnant women: A population‐based descriptive study from Denmark

Abstract: Purpose Antidepressants are the mainstay of pharmacological treatment for nonpsychotic mental disorders in the perinatal period. However, little is known about the indications for antidepressant use during pregnancy. We aimed to examine the treatment indications of antidepressant prescriptions redeemed by pregnant women and to investigate whether treatment indication patterns changed over time. Methods We conducted a population‐based descriptive study using Danish national registers. We identified pregnancies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…However, our study population included only pregnancies within women having received a clinical diagnosis for depression and/or anxiety and the majority of antidepressant prescriptions have depression and/or anxiety as an indication. 8 Third, we used consultation rate with psychiatric specialists as a proxy for non-pharmacological care which might have resulted in overestimation of the non-pharmacological care in pregnant women. However, specialists issued only 10% of antidepressant prescriptions while the number of consultations for depression/anxiety are similar to those of GPs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, our study population included only pregnancies within women having received a clinical diagnosis for depression and/or anxiety and the majority of antidepressant prescriptions have depression and/or anxiety as an indication. 8 Third, we used consultation rate with psychiatric specialists as a proxy for non-pharmacological care which might have resulted in overestimation of the non-pharmacological care in pregnant women. However, specialists issued only 10% of antidepressant prescriptions while the number of consultations for depression/anxiety are similar to those of GPs.…”
Section: Discussionmentioning
confidence: 99%
“…Table1. Characteristics of pregnancies included in the study population, Norway, 2009-2018 (8,460 pregnancies) Abbreviations: coef -coefficient, CI -confidence interval. Significant estimates are indicated in bold.…”
Section: Tables and Figuresmentioning
confidence: 99%
See 1 more Smart Citation
“…[26][27][28][29][30] A recent population-based study from Denmark, observed that the prescription of antidepressants was less common during pregnancy than before and after it in the period 1997 to 2016. 31 To our knowledge, only few previous studies have investigated trajectories of medication use during pregnancy. Hurault et al were the first researchers to study psychotropic drugs during pregnancy with longitudinal methods 23 and to describe use of anxiolytics.…”
Section: And the 2018 International Cochrane Reviewmentioning
confidence: 99%
“…Many studies have shown that the use of antidepressants decreases during the first 3 months of pregnancy 26–30 . A recent population‐based study from Denmark, observed that the prescription of antidepressants was less common during pregnancy than before and after it in the period 1997 to 2016 31 . To our knowledge, only few previous studies have investigated trajectories of medication use during pregnancy.…”
Section: Introductionmentioning
confidence: 99%